Max Weber on charisma and institution building : - Weber, Max (University of Chicago Press, 1968)
This selection from Max Weber's writings presents his variegated work from one central focus, the relationship between charisma on the one hand, and the process of institution building in the major fields of the social order such as politics, law, economy, and culture and religion on the other. That the concept of charisma is crucially important for understanding the processes of institution building is implicit in Weber's own writings, and the explication of this relationship is perhaps the most important challenge which Weber's work poses for modern sociology.